Between the right to intimacy and the personal data protection at the workplace and the supervisory power of the employee: Video-surveillance cameras - Corrales Melgarejo, Edwin Ricardo (2023)
This article analyzes the technological impact of videosurveillance cameras at the workplace on the fundamental right to the privacy of the workers and the right to the protection of personal data, as well as the scope or limits of the supervisory power of the employer in their use, according to the doctrinal and jurisprudential contributions in its regulation.